Integration of corporate technological foresight into the technological development management system in companies of oil and gas sector - A. O. Alekseev; V. Ya. Afanasev (Управление)
The experience of leading multinational players in conducting corporate technological foresight shows that the key to its successful implementation is effective integration with the existing corporate strategic planning system.The issue of identifying the most important and necessary measures for integrating foresight into the corporate governance system of oil and gas companies has been considered in the article. The elements of the corporate management system with which it is necessary to build interrelation and description of options for strategies, have been presented, recommendations for conducting foresight for each of them have been given. It has been noted, that the use of foresight research has a significant impact on the effectiveness of individual projects and on the efficiency of companies' activity as a whole.The results obtained have showed that the effectiveness of the results of foresight directly depends on the company’s readiness to conduct it and the level of maturity of scientific and technical processes of innovative development of the company. The directions of the company’s management system, that have a particularly strong impact on the effectiveness of the results of foresight research have been highlighted, as well as methods for assessing the company’s readiness to conduct foresight have been proposed. An assessment of the options for applying foresight research depending on the company’s chosen model of innovative development and innovative development program has been given. It has been noted, that the greatest effect is achieved with a proactive management model that allows you to fully use the tools of foresight research, resulting forecasts. Using foresight for active and passive models doesn't give any advantages for the company, it leads to additional costs. The relationship between foresight and the most common organizational management structures, currently used in Russian oil and gas companies, has been shown.